The red algal genus Titanophora (Schizymeniaceae, Nemastomatales) in the Gulf of Mexico - Gabriel, Daniela (2009)
ABSTRACT: "Titanophora (J. Agardh) Feldmann currently comprises nine species inhabiting tropical and subtropical waters worldwide. The genus is distinguished from other members of the Schizymeniaceae primarily by the calcification of the frond and the presence of an involucre surrounding the carposporophyte. The present study provides a characterization of four distinct Titanophora species that were dredged throughout the Gulf of Mexico. On the basis of comparative vegetative and reproductive morphology and chloroplast-encoded rbcL sequence analysis, a new record for the Gulf, T. submarina Bucher & J.N. Norris, and two species new to science in addition to T. incrustans (J. Agardh) Boergesen are recognized for the region."